Ethics and Cultural Policy in a Global Economy - Owen-Vandersluis, Sarah. author. aut Link
256 p.
Keywords: Sarah Owen Vandersluis critically examines approaches to cultural policy within the global economy. This study taps into the growing debate on ethical theory and International Political Economy. It challenges the normative positions of nationalists and welfare economists, before developing an alternative communitarian ethics for cultural policy in a global economy. The study concludes with an examination of the practical implications of this ethics in several case studies.